2003
DOI: 10.1046/j.0022-7722.2003.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the nucleus reticularis magnocellularis to the rat cervical cord using electrical stimulation and iontophoretic injection methods

Abstract: The aim of this study is to clarify the fiber distribution of the nucleus reticularis magnocellularis (NRMC) and adjacent areas in the rat spinal cord. Biotinylated dextran amine was injected iontophoretically through a glass capillary into the areas, in which a single cell responded to noxious electrical stimulation of the sciatic nerve and to a pinch of the thigh skin with multiple spikes. Labeled fibers descended bilaterally through the ventral funiculi of the medulla oblongata and then through the ventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Similar results were obtained in other retrograde tracer studies (Newman,1985; Kwiat and Basbaum,1992), although for the thoracic spinal cord a very strong ipsilateral predominance has been reported (Kausz,1991; Zhang et al,2000). In contrast to the general picture of bilateral symmetry obtained from retrograde tracing, results of anterograde tracing from the Gi and GiA indicate a marked ipsilateral predominance of axons and axon terminals in both white and gray matter, particularly for the GiA (Basbaum et al,1978; Zemlan et al,1984; Jones and Yang,1985; Watanabe et al,2003). As noted above with respect to projections to the cervical vs. lumbosacral spinal cord, a likely explanation of the apparent discrepancy in the degree of ipsilateral predominance in the anterograde vs. retrograde studies is that bulbospinal neurons may form a richer preterminal arbor ipsilaterally.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar results were obtained in other retrograde tracer studies (Newman,1985; Kwiat and Basbaum,1992), although for the thoracic spinal cord a very strong ipsilateral predominance has been reported (Kausz,1991; Zhang et al,2000). In contrast to the general picture of bilateral symmetry obtained from retrograde tracing, results of anterograde tracing from the Gi and GiA indicate a marked ipsilateral predominance of axons and axon terminals in both white and gray matter, particularly for the GiA (Basbaum et al,1978; Zemlan et al,1984; Jones and Yang,1985; Watanabe et al,2003). As noted above with respect to projections to the cervical vs. lumbosacral spinal cord, a likely explanation of the apparent discrepancy in the degree of ipsilateral predominance in the anterograde vs. retrograde studies is that bulbospinal neurons may form a richer preterminal arbor ipsilaterally.…”
Section: Discussionmentioning
confidence: 94%
“…However, there is some uncertainty about the relative density of projections to cervical vs. lumbosacral levels. Several authors have reported a rostrocaudal gradient, based on anterograde tracing and antidromic microstimulation, with heavier terminations in rostral than caudal segments (Peterson et al,1975; Basbaum et al,1976; Jones and Yang,1985; Watanabe et al,2003). However, injecting a retrograde tracer into spinal gray matter at rostral and more caudal levels, Skagerberg and Bjorklund (1985) found a roughly uniform density of bulbospinal projections throughout the length of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preganglionic neurons of the brainstem and spinal cord innervate the parasympathetic and sympathetic autonomic ganglia and the enteric nervous system which are directly related to cephalic, thoracic, abdominal and pelvic autonomic effectors. 24 , 43 - 46 These regions participate in the constitution of complex neural networks linking high-level cognitive and affective sites with lower integrating structures to influence autonomic, emotional and behavioral responses. 15 …”
Section: Methodsmentioning
confidence: 99%
“…It is heterogeneous in composition and contains multiple cell groups that are different in their neurochemical phenotype (e.g. rostroventrolateralis, gigantocellular nucleus, and paragigantocellularis lateralis [68–71] . Within the RVLM, the adrenergic group C1 neurons, alternatively known as adrenergic neurons, are defined based on their expression of phenylethanolamine-n-methyltransferase (PNMT) [72,73] .…”
Section: Cardiovascular Effects Of Cannabinoidsmentioning
confidence: 99%